The flood points distribution in Dibal Village from 2019 to 2023 - Iemaaniah, Zuhdiyah Matienatul; Qomariyatuzzamzami, Latifah Nurul; Zamani, Muhammad Zaki (UIN Sulthan Thaha Saifuddin Jambi, Pusat Kajian Lingungan Hidup, 2023)
Floods are natural disasters that commonly occur in tropical countries like Indonesia. Floods often happen in low-lying areas densely populated by residents. The amount and intensity of rainfall have a significant impact on the occurrence of floods at specific points. Population growth and urban development have led to rapid construction, reducing areas for rainwater absorption. This study was conducted in Dibal Village, Ngemplak District, Boyolali Regency, which directly borders Surakarta City. The area has three important facilities as supporting facilities for the region. This research aims to determine the distribution and causes of floods in Dibal Village over the past five years.This research utilized spatial data, analyzed qualitatively using a descriptive approach. Research data were obtained from in-depth interviews and presented in a flood distribution map of Dibal Village. The results of this study identified flood points in Beran Hamlet, North Dibal Hamlet, Central Dibal Hamlet, South Dibal Hamlet, and North Wangkis Hamlet. Among these hamlets, the most severely affected by floods is Beran Hamlet, with flood depths ranging from 30-50 cm and a receding time of 5-9 hours. Meanwhile, North Dibal Hamlet experienced flood depths of 10-30 cm with a receding time of 3-7 hours, Central Dibal Hamlet had flood depths of 10-20 cm with a receding time of 3-5 hours, South Dibal Hamlet had flood depths of 15-25 cm with a receding time of 3-5 hours, and North Wangkis Hamlet had flood depths of 10-25 cm with a receding time of 3-9 hours